2017
DOI: 10.1002/2017gl073132
|View full text |Cite
|
Sign up to set email alerts
|

Juno observations of large‐scale compressions of Jupiter's dawnside magnetopause

Abstract: We investigate the structure of Jupiter's dawnside magnetopause using observations obtained by particle and fields instrumentation on the Juno spacecraft. Characterization of Jupiter's magnetopause is critical for the understanding of mass and energy transport between the solar wind and the magnetosphere. We find an extended magnetopause boundary layer (MPBL) during a magnetopause crossing on 14 July 2016. This thick MPBL, in combination with a large magnetic field component normal to the magnetopause boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…Geophysical Research Letters ~0.01 cm À3 , with modest increases close to the magnetopause associated with the magnetopause boundary layer Gershman et al, 2017).…”
Section: /2018gl079118mentioning
confidence: 99%
“…Geophysical Research Letters ~0.01 cm À3 , with modest increases close to the magnetopause associated with the magnetopause boundary layer Gershman et al, 2017).…”
Section: /2018gl079118mentioning
confidence: 99%
“…Before Juno's first primary science orbit, JADE measured solar wind ions and magnetospheric ions and electrons with key structures identified in McComas et al [2017], evidence for magnetic reconnection in Ebert et al [2017], a very large hot flow anomaly in the solar wind [Valek et al 2017]. JADE also contributed to a study on magnetopause crossings [Gershman et al, 2017]. Szalay et al [2017] mapped the different regions sampled over the auroral regions to the equatorial magnetosphere for the first science orbit.…”
Section: Introductionmentioning
confidence: 99%
“…On board, it carries the Jovian Auroral Distributions Experiment (JADE), an instrument suite that consists of a single ion detector, JADE-I (0.01-50 keV/q), and two electron detectors, JADE-E (0.1-100 keV) [McComas et al, 2013]. Prior to Juno's first science perijove pass, JADE measured the inbound solar wind, magnetosheath, and magnetosphere [McComas et al, 2017], observed a hot flow anomaly [Valek et al, 2017], found evidence for magnetic reconnection at the magnetopause [Ebert et al, 2017], observed mass transport across the magnetopause [Gershman et al, 2017], and found evidence for a connection between solar wind inputs and auroral emissions [Nichols et al, 2017].…”
Section: Introductionmentioning
confidence: 99%